Application of simple biological analyses to screen irradiated brown rice, soybean and sesame seeds - Ahn, Jae-Jun; Shahbaz, Hafiz Muhammad; Park, Ki-Hwan; Kwon, Joong-Ho (Applied biological chemistry, 2014)
The efficacy of biological screening assays such as germination test and direct epiuorescent lter technique (DEFT) and aerobic plate count (APC) was evaluated to detect the irradiation status of different seeds. DEFT/APC help to calculate the difference between dead and living microorganisms in a sample after a possible irradiation treatment. Likewise, the irradiation can significantly affect the physiological and biochemical processes in germinating seeds, which provides the basis for the germination test. In the present study, three different seeds (brown rice, soybean, and sesame) of Korean and Chinese origins were subjected to gamma-irradiation (0.5, 1, 2, and 4 kGy) and the effects on the germination characteristics were evaluated. The results revealed that the growth rate and shoot length decreased with increasing irradiation doses. Particularly, 4 kGy of irradiation had a pronounced effect on all the germination characteristics in all seed samples. The DEFT counts did not change, which were independent of the irradiation dose, whereas the APC counts gradually decreased with dose increment. The results showed the potential of the germination test and DEFT/APC as useful screening methods for irradiated seeds.